Evolutionary pathways driven by female mate choice : the curious case of the squalius alburnoides allopolyploid fish complex - Morgado-Santos, Miguel (2018)
Tese de doutoramento, Biologia (Etologia), Universidade de Lisboa, Faculdade de Ciências, 2018